ChemInform Abstract: A Unified Bioinspired "Aplysinopsin Cascade": Total Synthesis of (.+‐.)‐Tubastrindole B and Related Biosynthetic Congeners. Issue 14 (April 2015) - Skiredj, Adam; Beniddir, Mehdi A.; Joseph, Delphine; Leblanc, Karine; Bernadat, Guillaume; Evanno, Laurent; Poupon, Erwan
Abstract: (.+‐.)‐Tubastrindole B (Ia) and a precursor of (.+‐.)‐tubastrindole E (Ib) are prepared by a ring‐expansion cascade of a dictazole‐type precursor.